Prasejarah Gunung Sewu - Simanjuntak, Truman; Handini, Retno, 1967-; Prasetyo, Bagyo, 1957- (Pasar Minggu, Jakarta : Ikatan Ahli Arkeologi Indonesia, 2008)
Prehistory and the archaeology of Sewu Mountains, Indonesia; collection of articles.
Includes bibliographical references (p. 271-281).
Keywords: Prehistoric peoples -- Indonesia -- Sewu Mountains; Antiquities, Prehistoric -- Indonesia -- Sewu Mountains; Sewu Mountains (Indonesia) -- Antiquities